Design and development of pneumatic compressed air vehicle. (2021) - Ramasubramanian, S.; Chandrasekaran, M.; Baskar, S.; Dowhithamaran, A.; Ravin,
Abstract: Conventional vehicles depend on crude energy extracted from the fossil fuels such as diesel and petrol, which undergoes internal combustion to liberate the chemical energy stored inside the fuel. This energy is then converted into mechanical energy inside the engine to produce the necessary work for propelling the vehicle accompanied with release of incomplete combustion products such as CO and CO2 . Now days a lot of research is concentrated on developing more efficient and eco-friendly ways of generating the energy for propulsion so as to reduce the amount of carbon footprint in the atmosphere. The present work is an effort in the direction of generation of energy for propelling the vehicles in an environmental friendly way by utilising compressed air. During the process of compression, work is being done on the air, which causes an increment in the total pressure of the air. This increment of the total pressure is stored as the energy inside the compressed air, which will be utilised for the running the vane of the motor to generate the necessary work for propulsion. The present work utilises the compressed air at 3 atm to run the motor. The work output of the motor for different vane angles was measured for various casing diameters of 50 mm, 100 mm, 150 mm respectively and the results were plotted. The average time of running of the motor was found out to be 7 h.